Psychological factors behind the lack of participation in online discussions. (February 2016) - Amichai-Hamburger, Yair; Gazit, Tali; Bar-Ilan, Judit; Perez, Oren; Aharony, Noa; Bronstein, Jenny; Sarah Dyne, Talia
Abstract: The majority of participants in online communities are lurkers, who browse discussions without actively contributing to them. Their lack of active participation threatens the sustainability of online communities. This review provides an understanding as to why the majority of participants in online communities remain silent. It specifies a variety of factors that come into play when people determine their level of participation: individual differences: need for gratification, personality dispositions, time available and self-efficacy; social-group processes: such as socialization, type of community, tendency toward social loafing, responses to delurking and the quality of responses; technological setting factors: technical design flaws, privacy and safety of the online group. All are factors that are liable to influence involvement in online communities. Highlights: This article provides an understanding as to why the majority of participants in online communities remain silent. This article specifies a variety of factors that come into play when determining various levels of participation. The paper suggests ways in which to encourage people to participate in online discussions.